2018
DOI: 10.1158/1538-7445.am2018-2431
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2431: EFNA3, a key functional mediator of hypoxic microenvironment in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of all cancer-related deaths. Its rapid proliferative nature and HCC specific therapy such as transarterial chemoembolization (TACE) that block arterial blood supply to the tumor frequently induce hypoxic microenvironments i.e. regions with oxygen deprivation. Hypoxia has emerged as a major driving force to promote aggressive phenotypes and stemness of cancer cells in solid tumors. We aimed to identify the key contributors to HCC progression in hypoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The candidate gene igf1ra, identified in this study, codes for IGF-1 receptor-a, a receptor of insulin-like growth factor that was reported to be a primary mediator of growth hormones [38]. The ephrin-A3 gene (efna3) is shown as a key functional mediator of hypoxic microenvironment and is regarded as a therapeutic target for hypoxia-specific disease [39]. Retinoic acid receptor-related orphan receptor alpha (rora) was demonstrated to be an important mediator of HIF-1α activities in human [40].…”
Section: Discussionmentioning
confidence: 88%
“…The candidate gene igf1ra, identified in this study, codes for IGF-1 receptor-a, a receptor of insulin-like growth factor that was reported to be a primary mediator of growth hormones [38]. The ephrin-A3 gene (efna3) is shown as a key functional mediator of hypoxic microenvironment and is regarded as a therapeutic target for hypoxia-specific disease [39]. Retinoic acid receptor-related orphan receptor alpha (rora) was demonstrated to be an important mediator of HIF-1α activities in human [40].…”
Section: Discussionmentioning
confidence: 88%
“…The candidate gene igf1ra, identified in this study, codes for IGF-1 receptor-a, a receptor of insulin-like growth factor that was reported to be a primary mediator of growth hormones [37]. The ephrin-A3 gene (efna3) is shown as a key functional mediator of hypoxic microenvironment and is regarded as a therapeutic target for hypoxia-specific disease [38]. Retinoic acid receptor-related orphan receptor alpha (rora) was demonstrated to be a key regulator of HIF-1α activities in human [39].…”
Section: Discussionmentioning
confidence: 88%